Merkel Cell Carcinoma: An Update and Immunotherapy - Uchi, Hiroshi (Frontiers in Oncology, 2018)
Merkel cell carcinoma (MCC) is a rare but aggressive skin cancer with frequent metastasis and death. MCC has a mortality rate of 30%, making it more lethal than malignant melanoma, and incidence of MCC has increased almost fourfold over the past 20 years in the United States. MCC has long been considered to be an immunogenic cancer because it occurs more frequently in immunosuppressed patients from organ transplant and HIV infection than in those with immunocompetent. Chronic UV light exposure and clonal integration of Merkel cell polyomavirus (MCPyV) are two major causative factors of MCC. Approximately 80% of MCC are associated with MCPyV, and T cells specific for MCPyV oncoproteins are present in the blood and tumors of patients. Several studies have shown that a subset of Merkel-cell carcinomas express PD-1 on tumor-infiltrating lymphocytes and express PD-L1 on tumor cells, which suggests an endogenous tumor-reactive immune response that might be unleashed by anti–PD-1 or anti–PD-L1 drugs.